Implementation of Financial Technology in The Quick Response (QR) Code Based Payment System Towards Customer Statisfaction at NTB Syariah Bank Pejanggik Main Branch - I Made Oka Suwartana Suwartana (IQTISHADUNA, 2023)
ABSTRACT This study aimed to discover and investigate the implementation of financial technology withQR Code-based payment system and its effect on customers’ satisfaction at NTB SyariahBank Pejanggik Main Branch. This descriptive qualitative study gathered data from interviewswith key informants to the likes of management and officers of the bank, the developmentteam of the technology division, Customers, and merchants/partners who have collaboratedwith the bank QRIS merchant services. The study concluded that the implementation offinancial technology has run well, and further development plans were needed to provideQRIS CPM (Customer Presented Mode) services, QRIS TTS (Tarik Transfer Deposit), andQRIS Issuer Cross Border. Customer satisfaction was measured through customers andmerchants who found it easier and safe payments as their reason for sustainably using andrecommending this feature to others. In addition, qualitative research enriched the knowledgeand perspectives of customers regarding the benefits and challenges faced using fintech, aQR Code-based payment system. Hence, the bank needed to improve socialization andliteracy for both customers and merchants to remain using cash transactions with the QRISof NTB Syariah Bank.